Intranet use in Hong Kong public hospitals - Fong, S.; Quaddus, Mohammed (Emerald Group Publishing, 2010)
Purpose – The purpose of this paper is to report the findings from a study of the relationships of organization support, user characteristics, task characteristics, and intranet characteristics for using intranet applications to support management accounting in public hospitals. Design/methodology/approach – To test the research hypotheses, data were collected from Hong Kong public hospitals using a questionnaire survey. The research attempts to identify how the interactions of these antecedents help to achieve intranet user information satisfaction (IUIS) and thus efficiency of management accounting in hospitals in terms of information quality of management accounting systems (MASIQ).Findings – The results show that IUIS is positively associated with IQMAS in Hong Kong public hospitals. User characteristics such as information systems (IS) experience is positively associated with IUIS, and the extent of task characteristics is also positively associated with the IQMAS. The results have several implications for accounting IS management. Research limitations/implications – The paper provides support for some prior research findings and some findings are not consistent with expectations. The paper is based on questionnaire responses of 157 hospital executives. The findings are then generalized to the population studied – Hong Kong public hospitals. More research is needed for exploration and confirmation of these findings.Practical implications – The research offers insights into management accounting and control systems as they are implemented through the use of intranet in public hospitals. It suggests that top management support is of prior concern in improving managerial performance. Originality/value – The paper bridges two disciplines of studies, management accounting and IS. The results provide some useful support of prior findings and some modifications and extensions that further understanding in this area.